Phylogenetic relationships among extinct and extant turtles: the position of Pleurodira and the effects of the fossils on rooting crown-group turtles - Sterli, Juliana (2010)
The origin and evolution of the crown-group of turtles (Cryptodira + Pleurodira) is one of the most interesting topics in turtle evolution, second perhaps only to the phylogenetic position of turtles among amniotes. The present contribution focuses on the former problem, exploring the phylogenetic relationships of extant and extinct turtles based on the most comprehensive phylogenetic dataset of morphological and molecular data analyzed to date. Parsimony analyses were conducted for different partitions of data (molecular and morphological) and for the combined dataset. In the present analysis, separate analyses of the molecular data always retrieve Pleurodira allied to Trionychia. Separate analysis of the morphological dataset, by contrast, depicts a more traditional arrangement of taxa, with Pleurodira as the sister group of Cryptodira, being Chelonioidea the most basal cryptodiran clade. The simultaneous analysis of all available data retrieves all major extant clades as monophyletic, except for Cryptodira given that Pleurodira is retrieved as the sister group of Trionychia. The paraphyly of Cryptodira is an unorthodox result, and is mainly caused by the combination of two factors. First, the molecular signal allies Pleurodira and Trionychia. Second, the morphological data with extinct taxa locates the position of the root of crown-group Testudines in the branch leading to Chelonioidea. This study highlights major but poorly explored topics of turtle evolution: the alternate position of Pleurodira and the root of crown turtles. The diversification of crown turtles is characterized by the presence of long external branches and short internal branches (with low support for the internal nodes separating the major clades of crown turtles), suggesting a rapid radiation of this clade. This rapid radiation is also supported by the fossil record, because soon after the appearance of the oldest crown-group turtles (Middle-Late Jurassic of Asia) the number and diversity of turtles increases remarkably. This evolutionary scenario of a rapid diversification of modern turtles into the major modern lineages is likely the reason for the difficulty in determining the interrelationships and the position of the root of crown-group turtles.